PEMANFAATAN GOOGLE CLASSROOM SEBAGAI SARANA PEMBELAJARAN DI SD KRISTEN SATYA WACANA - Djari, Maria Cristiana Yuliyanti; Iriani, Ade; Satyawati, Sophia Tri (Satya Widya, 2022)
This research aims to analyze the use of Google Classroom as a learning tool at Satya Wacana Christian Elementary School, those are; (1) whether the existence of ICT helps in teaching, (2) how effective and interactive the use of Google Classroom is as a learning tool, (3) what features are often used, (4) explain the advantages of Google Classroom, and (5) the obstacles faced when using Google Classroom as a learning tool at Satya Wacana Christian Elementary School. This research used a qualitative descriptive method by conducting interviews and distributing questionnaires. The research subjects are 12 teachers at Satya Wacana Christian Elementary School. Based on the results of observations, interviews, and questionnaires, it was found that 100% of teachers felt that ICT was very helpful in teaching, 83.3% of teachers stated that the use, interaction, and assessment in Google Classroom were considered effective in their implementation, 100% of teachers often used Google Forms, the rest were Google Docs. , Slides, and Spreadsheets, 83.3% of respondents stated that GC is easy to use, 66.6% said GC’ features are complete, and 50% of respondents stated that GC is more effective and flexible. The obstacles that are often faced when using GC are the lack of stability of the internet network, there are still students who do not have their own gadget/computer/laptop facilities, charging grades that are still not appropriate, and limited video transmission capacity.